Structural insights into understudied human cytochrome P450 enzymes. Issue 10 (October 2021) - Machalz, David; Pach, Szymon; Bermudez, Marcel; Bureik, Matthias; Wolber, Gerhard
Highlight: This review provides an overview on structural investigations of understudied CYPs. We discuss the role of understudied CYPs as potential novel drug targets. We highlight the value of homology models to structurally access understudied CYPs. Molecular dynamics simulations help to mechanistically understand enzymatic activity. Dynamic pharmacophores are a powerful novel tool for elucidating ligand recognition. Abstract: Human cytochrome P450 (CYP) enzymes are widely known for their pivotal role in the metabolism of drugs and other xenobiotics as well as of endogenous chemicals. In addition, CYPs are involved in numerous pathophysiological pathways and, hence, are therapeutically relevant. Remarkably, a portion of promising CYP targets is still understudied and, as a consequence, untargeted, despite their huge therapeutic potential. An increasing number of X-ray and cryo-electron microscopy (EM) structures for CYPs have recently provided new insights into the structural basis of CYP function and potential ligand binding. This structural knowledge of CYP functionality is essential for both understanding metabolism and exploiting understudied CYPs as drug targets. In this review, we summarize and highlight structural knowledge about this enzyme class, with a focus on understudied CYPs and resulting opportunities for structure-based drug design. Teaser: This review summarizes recent structural insights into understudied cytochrome P450 enzymes. We highlight the impact of molecular modeling for mechanistically explaining pathophysiological effects establishing understudied CYPs as promising drug targets.